Hamstring Muscle Flexibility among KONI Volleyball Players of DKI Jakarta Province – A Pilot Study for Sport Injury Prevention. - Hendriko; Tirza Z Tamin; I Nyoman Murdana; Aria Kekalih (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: To find hamstring muscle flexibility among KONI Propinsi DKI Jakarta’s volleyball players,based on age, sex and playing position particularly.Methods: A cross sectional study performed in 25 female and 24 male athletes using Sit and Reach Test (SRT) box had done 3 times trial with the best score was recorded.Results: Hamstring muscle’s mean value score was 18.21 (SD 6.5) cm, male athletes was 17.6 (SD 6.5) cm, female athletes was 18.8 (SD 6.6) cm, middle adolescence 14-16 years old was 15.55 (SD 6.1) cm,late adolescence 17-20 years old was 19.91 (SD 6.9) cm, young adulthood 21-24 years old was 18.79 (SD 4.6) cm, hitter was 18.8 (SD 6.6) cm, center was 15.5 (SD 6.3) while allround players was 20.4 (SD5.9).Conclusions: Average value of hamstring flexibility among volleyball athletes of KONI DKI Jakarta based on SRT was 18.21 ± 6.5 cm, particularly within middle adolescence (14-16 years old) was 15.55± 6.1 cm, late adolescence (17-20 years old) was 19.91 ± 6.9 cm, and young adulthood (21-24 year old) was 18.79 ± 4.6 cm. While by sex was 17.6 ± 6.5 cm among male and 18.8 ± 6.6 cm among female.Based on playing position, hitters were 18.8 ± 6.6, setters were 15.5 ± 6.3 and all-round player were 20.4 ± 5.9 cm.Keywords: Flexibility, Hamstring muscle, SRT